2020
DOI: 10.1101/2020.01.23.916155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Establishment gaps in species-poor grasslands: artificial biodiversity hotspots to support the colonization of target species

Abstract: Sowing of grass seed mixtures is a feasible and cost-effective method for landscape-scale grassland restoration. However, sowing only grasses usually leads to species-poor and dense grass sward, where the establishment of target forbs is hampered both by microsite and propagule limitation. To overcome these limitations and increase the diversity of species-poor sown grasslands we developed a novel method by creating 'establishment gaps'. We used tillage to open gaps of 1 m 2 , 4 m 2 and 16 m 2 size in the dens… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The soil of disturbed sites generally contains high numbers of seeds of annuals and/or ruderal species (Bischoff, 2002; Donath et al, 2007). These species often dominate the vegetation of early successional stages before being replaced by typical grassland species that are usually perennials developing later in the succession (Kiehl et al, 2010; Valkó et al, 2016; Kiss et al, 2020). The first year after the restoration of Eastern European grasslands, Lengyel et al (2012) observed that annual weeds were dominant, but the cover of those weeds decreased dramatically after the third year due to the growth of perennial grasses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil of disturbed sites generally contains high numbers of seeds of annuals and/or ruderal species (Bischoff, 2002; Donath et al, 2007). These species often dominate the vegetation of early successional stages before being replaced by typical grassland species that are usually perennials developing later in the succession (Kiehl et al, 2010; Valkó et al, 2016; Kiss et al, 2020). The first year after the restoration of Eastern European grasslands, Lengyel et al (2012) observed that annual weeds were dominant, but the cover of those weeds decreased dramatically after the third year due to the growth of perennial grasses.…”
Section: Discussionmentioning
confidence: 99%
“…Poor seed dispersal, as well as the lack of connectivity between source populations due to landscape fragmentation, often limit the seed rain (Münzbergová & Herben, 2005; Bischoff et al, 2009; Muller et al, 2014) and successful restoration may require seed addition to overcome seed limitation (Öster et al, 2009; Török et al, 2012; Valkó et al, 2016). Thus, seed addition methods, such as sowing local seed mixtures, hay transfer or soil transfer, are increasingly used in grassland restoration (Kiehl et al, 2010; Scotton et al, 2012; Kiss et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Site treatments prior to seeding may be required to remove or reduce competition with undesirable species, increase site stability, repair hydrologic function, or reduce nutrient levels (Morgan 2005). Seedbed preparation operations may then be required to produce physical disturbance of the germination substrate and provide establishment niches (Schmiede et al 2012; Kiss et al 2020). Tillage, herbicide application, prescribed fire, and other treatments can be used to create seedbed conditions appropriate to the species and seed delivery system (Whisenant 1999; Morgan 2005; Krautzer et al 2012; Armstrong et al 2017).…”
Section: Site Treatments and Seedbed Preparationmentioning
confidence: 99%
“…These operations can be conducted to increase species diversity, alter community structure across a site, or restore depleted or weed‐infested areas (Rayburn & Laca 2013; Silva et al 2019). Diversification of species‐poor native vegetation or seedings is often hampered by microsite limitations (Münzbergová & Herben 2005); disturbance to reduce competition or improve microsite availability is often necessary before species introduction occurs (Schmiede et al 2012; Baasch et al 2016; Kiss et al 2020).…”
Section: Seed Deliverymentioning
confidence: 99%
“…Therefore, sowing seeds of rare target species is a widely applied species introduction method in dry grassland restoration projects (Barr et al 2017). However, the availability of seed material of regional provenance is often a major limiting factor in restoration projects (de Vitis et al 2017), and especially in large‐scale projects only a limited number of target species can be included in the seed mixtures (Kiss et al 2020).…”
Section: Introductionmentioning
confidence: 99%